Pendampingan Pembelajaran Masa Pandemi Siswa TK Dan SD Desa Bleber Kras Kediri - Yuliatus Sa'adah; Nurmahmudah Nurmahmudah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This activity is based on the fact that online learning is caused by the outbreak of the covid 19 outbreak. In this case, the aim is to increase the ability, understanding, and enthusiasm of kindergarten and elementary school students in online learning. The target is Kindergarten and Elementary School students in Bleber Kras Kediri Village using discussion methods and learning assistance. This activity was carried out in 10 meetings and each meeting lasted for 3 hours. When the activity takes place, the study group is limited to five children per hour, and in a day there are three groups that take tutoring. As a result, students began to enthusiastically carry out online learning and also parents of students participated in supporting tutoring activities during this pandemic in Bleber Kras Village, Kediri. Students are also more assisted in carrying out tasks from school.